Recent scientific data on the treatment of female infertility of tubal origin - Marana, Riccardo; Vanzetto, Mariacristina; Mancuso, Salvatore (Medicina e Morale, 2024)
In 1976 in the United States about 10-15% of couples failed to conceive after at least one year of marriage without the use of contraceptive methods. At the same time, the number of visits to private doctors for infertility problems increased from about 600,000 in 1968 to about 900,000 in 1980. This increased concern about infertility problems appears to be concentrated in that cohort of the American female population born after World War II, currently in their thirties or early forties.